Pendidikan Global Dengan Berbagai Isu Dalam Perspektif Pendidikan Islam - Indra Taupik Saleh; Ahmad Husni; Uus Ruswandi; Mohamad Erihadiana (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of the study was to find out how the ability to write job application letters for class XII students of SMK Negeri 2 Depok City in 2019-2020 and to find out whether cooperative learning with the Think-Pair-Share model could improve the ability to write cover letters for class XII students of SMK Negeri 2 Depok City. This study uses classroom action research (action research) in two rounds (cycles). Each round consists of four stages, namely: planning, activities and observations, reflection, and revision. The target of this research is Class XII Computer Network Engineering (TKJ) SMK Negeri 2 Depok City in 2019-2020. The data obtained in the form of subjective test results and observation sheets of teaching and learning activities. The results show, class XII students of TKJ SMK Negeri 2 Depok City in 2019-2020 are able to write job applications. This can be seen from the average score of students' ability to write job application letters and student learning completeness in cycle I and cycle II has increased. The average score of students' ability to write job application letters in the first cycle was 72.77 and learning completeness reached 64.70%. The average score of students' ability to write job application letters in cycle II was 78.38 and learning completeness reached 85.29%. The application of the Think-Pair-Share model of cooperative learning has a positive influence on Teaching and Learning Activities (KBM). Think-Pair-Share model of cooperative learning can improve student learning outcomes. This is indicated by the average student answers stating that students are interested and interested in the Think-Pair-Share cooperative learning method so that they become motivated to learn. Keywords: Writing Ability, Cooperative Learning, Think-Pair-Share Learning Model